Wreck Removal: An analysis between brazilian maritime law and the Nairobi International Convention on the Removal of Wrecks - Nogueira Camacho, Wellington (Revista de Direito e Negócios Internacionais da Maritime Law Academy - International Law and Business Review, 2021)
The present work aims to carry out a comparative analysis between the Wreck Removal Convention and Law Nº. 7,542 / 1986, which deals with the same subject in Brazilian Jurisdictional Waters, emphasizing the need to ensure the prevention of the marine environment as well as the existence of risk insurance and other financial guarantees to contemplate the removal of wrecks in the face of a maritime casualty.